The Sixth Evaluation Report on Working of Community Development and N. E. S. Blocks - Planning Commission (Planning Commission, 1959)
The present report, the sixth, on the Evaluation of the Community Development Programme follows the practice adopted last year. Instead of attempting an overall review of the programme, we have selected a few important aspects and dealt with them rather more fully. Last year’s report covered panchayats, agricultural practices and the Village Level Worker’s records, besides general issues of block administration. The present report is made up of studies on the planning process at the block and the village levels, pilot projects for cottage industries, large and small cooperative societies and social education. The importance of these topics should be obvious to the reader. The Community Development Programme was sponsored by the Government and is still largely administered by the bureaucracy. But the accepted objective is to make it a people’s movement, with the villagers taking over the responsibility for framing and executing the plans for local development. This requires, on the one hand, democratization and strengthening of the local institutions and training of the rural people for their new responsibility and on the other, reorientation of the official, and readjustment' of his relations with the common man in the village.
Programme Evaluation Organisation Planning Commission